Targeting neutrophils using novel drug delivery systems in chronic respiratory diseases. Issue 4 (12th February 2020) - Chellappan, Dinesh K.; Yee, Lim W.; Xuan, Kong Y.; Kunalan, Kishen; Rou, Lim C.; Jean, Leong S.; Ying, Lee Y.; Wie, Lee X.; Chellian, Jestin; Mehta, Meenu; Satija, Saurabh; Singh, Sachin K.; et al.
Abstract: Neutrophils are essential effector cells of immune system for clearing the extracellular pathogens during inflammation and immune reactions. Neutrophils play a major role in chronic respiratory diseases. In respiratory diseases such as asthma, chronic obstructive pulmonary disease, cystic fibrosis, lung cancer and others, there occurs extreme infiltration and activation of neutrophils followed by a cascade of events like oxidative stress and dysregulated cellular proteins that eventually result in apoptosis and tissue damage. Dysregulation of neutrophil effector functions including delayed neutropil apoptosis, increased neutrophil extracellular traps in the pathogenesis of asthma, and chronic obstructive pulmonary disease enable neutrophils as a potential therapeutic target. Accounting to their role in pathogenesis, neutrophils present as an excellent therapeutic target for the treatment of chronic respiratory diseases. This review highlights the current status and the emerging trends in novel drug delivery systems such as nanoparticles, liposomes, microspheres, and other newer nanosystems that can target neutrophils and their molecular pathways, in the airways against infections, inflammation, and cancer. These drug delivery systems are promising in providing sustained drug delivery, reduced therapeutic dose, improved patient compliance, and reduced drug toxicity. In addition, the review also discusses emerging strategies and the future perspectives in neutrophil‐based therapy.